Antiretroviral therapy initiation and outcomes of hospitalized HIV-infected patients in Uganda-An evaluation of the HIV test and treat strategy. - Andrew Katende; Lydia Nakiyingi; Irene Andia-Biraro; Thomas Katairo; Richard Muhumuza; Andrew S Ssemata; Christopher Nsereko; Fred C Semitala; David B Meya (PLoS ONE, 2022)
Background Uganda adopted the HIV Test and Treat in 2016. There is paucity of data about its implementation among hospitalized patients. We aimed to determine the proportion of patients initiating anti-retroviral therapy (ART) during hospitalization, barriers and mortality outcome. Methods In this mixed methods cohort study, we enrolled hospitalized patients with a recent HIV diagnosis from three public hospitals in Uganda. We collected data on clinical characteristics, ART initiation and reasons for failure to initiate ART, as well as 30 day outcomes. Healthcare workers in-depth interviews were also conducted and data analyzed by sub-themes. Results We enrolled 234 patients; females 140/234 (59.8%), median age 34.5 years (IQR 29-42), 195/234 (83.7%) had WHO HIV stage 3 or 4, and 74/116 (63.8%) had CD4 ≤ 200 cell/μL. The proportion who initiated ART during hospitalization was 123/234 (52.6%) (95% CI 46.0-59.1), of these 35/123 (28.5%) initiated ART on the same day of hospitalization, while 99/123 (80.5%) within a week of hospitalization. By 30 days 34/234 (14.5%) (95% CI 10.3-19.7) died. Patients residing ≥ 35 kilometers from the hospital were more likely not to initiate ART during hospitalization, [aRR = 1.39, (95% CI 1.22-1.59). Inadequate patient preparation for ART initiation and advanced HIV disease were highlighted as barriers of ART initiation during hospitalization. Conclusion In this high HIV prevalence setting, only half of newly diagnosed HIV patients are initiated on ART during hospitalization. Inadequate pre-ART patient preparation and advanced HIV are barriers to rapid ART initiation among hospitalized patients in public hospitals.